Manipulation of optical nonreciprocity in hot atom-cavity system. (18th November 2021) - Zhou, Hai-Tao; Xie, Shu-Yun; Li, Xin; Wang, Dan; Yang, Bao-Dong; Zhang, Jun-Xiang
Abstract: Hot atoms can exhibit non-magnetic optical non-reciprocal transmission due to their chiral properties, which are characteristic of most alkali metal atoms. In fact, the nonreciprocity in hot atoms depends on the propagation direction of the coupling field due to the Doppler effect. Herein, the reciprocal to non-reciprocal conversion based on the single- and double-dark states is realized by controlling the bidirectional coupling fields in a three-level electromagnetically induced transparent medium coupled with a ring cavity. Tuning the frequency difference between the two coupling fields causes the multi-frequency-channel reciprocity and nonreciprocity manipulation to occur. The experimental proof can be applied to quantum communications and quantum networks, such as optical transistors, all-optical switching or routing and logic gate operation.